Assisted suicide in Italy: constitutional right or wishful thinking? (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The Italian Constitutional Court has surprised many commentators by making a provisional decision declaring the crime of assisted suicide unconstitutional, under certain conditions. Before officially striking down the article of the criminal code, however, the Court (following the Canadian example) gave the Parliament one year to enact a comprehensive law on the topic. The deadline is running out and the picture is far from clear: given the complexity of the legal system and the inertia of the Parliament, the right of sick and suffering people to be aided in taking their life is likely to remain, at least for a while, wishful thinking.
Keywords: Assisted suicide; euthanasia; end of life issues; constitutional law; Italy